Case Report: Simultaneous covered stenting for aortic coarctation and significant PDA in low and very low birth weight preterm infants: technical insights from two cases - Mini, Nathalie; Schindler, Ehrenfried; Breuer, Katinka; Mikus, Marian; Schneider, Martin B. E. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundTo the best of our knowledge, no study to date has reported the use of covered stents in preterm and low weight (LW) preterm babies for the combined treatment of aortic coarctation (CoA) and persistent patent ductus arteriosus (PDA) in these critically ill patients.Patients and methodsIn 2023, two premature infants with isolated critical CoA and a window-shaped PDA were treated with Biotronik PK Papyrus covered coronary stents. The indications for intervention in the first patient included a significant, short PDA with respiratory deterioration and necrotizing enterocolitis (NEC), despite prior CoA treatment using a premounted coronary stent and ongoing ibuprofen therapy, which failed to close the PDA. The second patient presented with impaired left-ventricular (LV) function, renal insufficiency, and NEC. Echocardiography was used both to assess the outcome of the intervention and for follow-up. The patency of the PDA was documented at 12 and 24 h postintervention.ResultsPatient 1, with a gestational age (GA) of 32 weeks and a birth weight of 1,400 g, and Patient 2, with a GA of 30 weeks and a birth weight of 1,900 g, underwent the procedure at 20 and 11 days of age, respectively. Both patients successfully received a PK Papyrus covered stent implantation. Angiographic imaging immediately following the intervention revealed evidence of a residual shunt in each patient. However, at 12 h postprocedure, no residual PDA shunt was detected on echocardiography. Both patients underwent successful surgical repair 7 and 10 months later, with complete removal of the 15 mm stents.ConclusionIn our rare and small cohort, covered stenting for CoA and PDA proved effective and safe in low-weight and very-low-weight premature infants, improving coarctation, achieving complete PDA closure, and offering the potential for full stent removal. The small sample size reflects the cohort's critical specificity, and the findings require validation in larger populations.